Pelatihan Membuat Sitasi Karya Ilmiah Mahasiswa Menggunakan Aplikasi Mendeley - Rofiatun Nisa' (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2022)
Obstacles that often arise in the presentation of written and scientific works are not being careful in including quotations and finding it difficult to manage reference sources. If the references listed have enough sources, the citation must also be clear according to what he quoted from the original source. The purpose of writing citation sources and bibliography is so that we avoid plagiarism. One of the functions of quotations is to support or reinforce our writing. The method used in the implementation of this service is an intensive mentoring method with direct practice on the Mendeley desktop application. The results of the mentoring in the form of Mendeley training were obtained in the pre-test session, the test participants only got an average of 62.75. Meanwhile, after the assistance, the score increased significantly, the average score was 96.25. This shows that what they know in making references to scientific papers is still inadequate before the training is carried out. After the implementation of the training, it was seen that their knowledge increased significantly.